Analyses of transcriptome sequences reveal multiple ancient large‐scale duplication events in the ancestor of Sphagnopsida (Bryophyta). Issue 1 (22nd February 2016) - Devos, Nicolas; Szövényi, Péter; Weston, David J.; Rothfels, Carl J.; Johnson, Matthew G.; Shaw, A. Jonathan
Summary: The goal of this research was to investigate whether there has been a whole‐genome duplication (WGD) in the ancestry of Sphagnum (peatmoss) or the class Sphagnopsida, and to determine if the timing of any such duplication(s) and patterns of paralog retention could help explain the rapid radiation and current ecological dominance of peatmosses. RNA sequencing (RNA‐seq) data were generated for nine taxa in Sphagnopsida (Bryophyta). Analyses of frequency plots for synonymous substitutions per synonymous site ( K s ) between paralogous gene pairs and reconciliation of 578 gene trees were conducted to assess evidence of large‐scale or genome‐wide duplication events in each transcriptome. Both K s frequency plots and gene tree‐based analyses indicate multiple duplication events in the history of the Sphagnopsida. The most recent WGD event predates divergence of Sphagnum from the two other genera of Sphagnopsida. Duplicate retention is highly variable across species, which might be best explained by local adaptation. Our analyses indicate that the last WGD could have been an important factor underlying the diversification of peatmosses and facilitated their rise to ecological dominance in peatlands. The timing of the duplication events and their significance in the evolutionary history of peat mosses are discussed.